Wood Texture as An Inspiration for the Creation of Digital Imaging - Yuwono, Budi (Indonesian Journal of Visual Culture, Design, and Cinema, 2022)
In the world of design, themes and concepts become fundamental. Themes and concepts cover the whole idea of a work, as well as in the field of digital imaging. Ideas can be taken from nearby environments such as natural beauty of wood texture. The idea used in the creation of digital imaging is wood texture. The process is the pre-production and production stage. Methods consisting of idea stages, data collection, stage of embodiment, and finalization. At the idea stage, it is attempted to visualize and represent the wood texture through digital imaging techniques. This idea was raised based on believes that wood texture has the aesthetic textures to be applied to digital imaging illustration. Data collection is done through observation. While at the stage of embodiment the process carried out is to make editing image through Adobe Photoshop software. Finalization done with export the illustration in JPG format. The result of this creation is an illustrative work resulting from the digital imaging process entitled Dream Land. It is the process of uniting and editing multiple images into one relevant entity.